Estimating Dynamic Games of Electoral Competition to Evaluate Term Limits in US Gubernatorial Elections - Sieg, Holger; Yoon, Chamna (American Economic Review, 2017)
This paper shows how to identify and estimate, using standard semi-parametric techniques, a class of dynamic games with perfect monitoring, that have been at the frontier of recent research in political economy. The empirical analysis provides novel quantitative insights into the trade-off that voters face between ideology and ability, the differences in ability and ideology among parties and states, and the differences in preferences between political candidates and voters. We analyze the consequences of term limits and quantify their relative importance. Specifically, we characterize conditions under which term limits improve voters' welfare. (JEL C57, C73, D72)